The morphogenetic capability and the viability of regenerants in micropropagated orchid hybrids infected with viral pathogens - Cybularz-Urban Teresa; Hanus-Fajerska Ewa (Folia Horticulturae, 2008)
The micropropagation efficiency of four interspecific Cattleya hybrids (clones: 69, 75, 149 and 150) infected with Cymbidium mosaic (CyMV) and Odontoglossum ringspot (ORSV) viruses was assessed. The aim of experiments was to evaluate with that model to what extent viral infection affects the morphogenesis in vitro in orchid hybrids of different origin. The effectiveness of plant material exposure to therapeutic levels of plant growth regulators supplied with media in order to suppress infection was also verified. The vitality of proliferating infected shoot cultures was limited, and the symptoms of senility were frequently observed. Regardless genotype of the studied clone, during acclimation to ex vitro conditions considerable losses become visible what indicates the necessity of testing the donor material for possible latent viral infections. Infection with CyMV and ORSV mostly persisted in every tested clone.